PENCATATAN KEUANGAN SEDERHANA DALAM MENINGKATKAN KINERJA BISNIS PARA SANTRI PADA PONDOK PESANTREN YATIM DAN DUAFA “NURUL HIKMAH” DESA LANGKO KECAMATAN LINGSAR - Yuliandari, Rini; Suharti, Suharti; Apriansyah, Roli; Netrawati, I Gusti Ayu Oka; Permadi, I Gusti Agung Didit Eka; Renaldi, Muhammad; Amta, An (LPPM Institut Pendidikan Nusantara Global, 2023)
The service carried out is the socialization of simple financial management in improving the business performance of students at the Nurul Hikmah Orphan and Dhuafa Islamic Boarding School in Village, Lingsar District. Therefore, this community service focuses on improving simple financial management. The target of this community service is students in Islamic Boarding Schools in order to improve the business performance of the students. In running a good business, financial reports must be prepared. This is to look at financial performance so that it can provide information on various financial positions, performance and cash flows, so that it can be used as a benchmark in making economic decisions. The aim of this socialization is to understand the importance of financial reports and design simple financial reports for students at the Nurul Hikmah orphan and Dhuafa Islamic boarding school in Langko Village, Lingsar District. The impact of socializing the preparation of financial reports provides an understanding of how to record finances in order to manage finances in business better and more effectively. The results of this socialization had a positive impact on participants so that they could understand and have skills in simple financial recording.